Migrazione, inclusione, sicurezza: un profilo di rischio per il nostro paese - Tusini, Stefania (SocietàMutamentoPolitica, 2020)
The essay aims to connect issues related to inclusion and security by examining the Italian case in which, in the face of poor inclusion policies, there is the absence of significant terrorist attacks. This peculiarity has raised several questions and will be discussed by looking at various factors that have probably protected the country and by evaluating the persistence of their effectiveness over time. In light of these considerations, the essay ends resuming the link between inclusion and security and outlining a risk profile for our country.